Contesting Language Ideologies in the Linguistic Schoolscapes in an Indonesian Multilingual School: A Case Study - Lestianingsih, Dwi; Nurkamto, Joko; Sumardi, Sumardi (VELES Voices of English Language Education Society, 2023)
The educational institution serves as a platform where diverse language ideologies intersect, particularly within multilingual schools. These language ideologies can shape how students perceive and use languages and influence policies and practices within the institution. Understanding and navigating these intersections is crucial for promoting inclusive and equitable language education. This study examines the perception of language ideological contests within the linguistic schoolscape of a multilingual country, specifically Indonesia. This article utilizes a triad model proposed by Lefebvre (1991) and Trumper-Hecht (2010) as its conceptual framework and employs the linguistic landscape as its methodological tool. The analysis focuses on school signs within a multilingual school setting. The findings suggest that Indonesian, English, and Chinese languages are employed within educational environments. The prevailing ideologies observed within this educational environment encompass globalization, ethnic identity, and nationality. These ideologies influence the choice of languages taught and prioritized in the curriculum and the attitudes and expectations toward each language.